2021
DOI: 10.3171/2020.8.peds20477
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of cerebrospinal fluid shunt valves in pediatric hydrocephalus: an analysis of cost, operative time, length of stay, and shunt failure

Abstract: OBJECTIVECSF shunts are the most common procedures performed in the pediatric neurosurgical population. Despite attempts in multiple studies, a superior shunt valve has never been shown. Because of this, the authors aim was to examine the impact of shunt valve standardization at their institution to determine if there is a difference in surgical cost, operative time, or short-term postoperative shunt failure.METHODSA retrospective analysis at the authors’ institution was performed for all new CSF diversion shu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Unexplained clinical variance may be at the root of our country's high healthcare costs and suboptimal outcomes compared to the rest of the world. 1 It is up to all of us as physicians and surgeons to use our clinical and business acumen to lead change and effect improvement on each side of the "iron triangle" of healthcare-access, quality, and cost. 2…”
Section: Responsementioning
confidence: 99%
See 4 more Smart Citations
“…Unexplained clinical variance may be at the root of our country's high healthcare costs and suboptimal outcomes compared to the rest of the world. 1 It is up to all of us as physicians and surgeons to use our clinical and business acumen to lead change and effect improvement on each side of the "iron triangle" of healthcare-access, quality, and cost. 2…”
Section: Responsementioning
confidence: 99%
“…The design of the study reported by Berns et al 1 limits the strength of any conclusions. Despite a 62.5% increase in the percentage of revisions and a 75% increase in the number of infections in the poststandardization group, the authors report no statistical differences between the groups.…”
mentioning
confidence: 96%
See 3 more Smart Citations